Multivehicle Cooperative Local Mapping: A Methodology Based on Occupancy Grid Map Merging - Hao Li; Tsukada, Manabu; Nashashibi, Fawzi; Parent, Michel (IEEE Transactions on Intelligent Transportation Systems, 2014)
Local mapping is valuable for many real-time applications of intelligent vehicle systems. Multivehicle cooperative local mapping can bring considerable benefits to vehicles operating in some challenging scenarios. In this paper, we introduce a method of occupancy grid map merging, dedicated to multivehicle cooperative local mapping purpose in outdoor environments. In a general map merging framework, we propose an objective function based on occupancy likelihood and provide some concrete procedures designed in the spirit of genetic algorithm to optimize the defined objective function. Based on the introduced method, we further describe a strategy of indirect vehicle-to-vehicle (V2V) relative pose (RP) estimation, which can serve as a general solution for multivehicle perception association. We present a variety of experiments that validate the effectiveness of the proposed occupancy grid map merging method. We also demonstrate several useful application examples of the indirect V2V RP estimation strategy.